Physical forces regulating hemostasis and thrombosis: Vessels, cells, and molecules in illustrated review. Issue 5 (14th July 2021) - Lin, Jessica; Sorrells, Matthew G.; Lam, Wilbur A.; Neeves, Keith B.
Abstract: This illustrated review focuses on the physical forces that regulate hemostasis and thrombosis. These phenomena span from the vessel to the cellular to the molecular scales. Blood is a complex fluid with a viscosity that varies with how fast it flows and the size of the vessel through which it flows. Blood flow imposes forces on the vessel wall and blood cells that dictates the kinetics, structure, and stability of thrombi. The mechanical properties of blood cells create a segmented flowing fluid whereby red blood cells concentrate in the vessel core and platelets marginate to the near‐wall region. At the vessel wall, shear stresses are highest, which requires a repertoire of receptors with different bond kinetics to roll, tether, adhere, and activate on inflamed endothelium and extracellular matrices. As a thrombus grows and then contracts, forces regulate platelet aggregation as well as von Willebrand factor function and fibrin mechanics. Forces can also originate from platelets as they respond to the external forces and sense the stiffness of their local environment.